How to place European Research Universities in the global rankings? Policies and strategies of University International Excellence in France and Spain - Casani, Fernando; Perez-Esparrells, Carmen; Petit, Jean-Claude; de la Torre García, Eva María (Advances in Social Sciences Research Journal, 2014)
Although global rankings do not classify national university systems, the majority of countries are reformulating their HE policies to improve the ranking position of their best universities. Accordingly, this paper studies the case of France and Spain through the analysis of their respective national policies for the promotion of university international excellence (state-level response to global rankings). In particular, we discuss two initiatives of university collaboration (institutional-level response to global rankings) aimed to create synergies and increase the international visibility of the participant institutions: the new branded university Paris Sciences et Lettres (PSL) and the Campus of International Excellence of the Universidad Autónoma de Madrid and the Spanish Research Council (CEI UAM+CSIC). In both case studies the participant institutions keep their autonomy and legal personality, a difficult alliance formula to administrate. Nevertheless, they are good practices that reflect a wide state-run strategy for the modernization of both national university systems.